2018
DOI: 10.2147/cmar.s168374
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnostic value of <sup>18</sup>F-FDG PET/CT for benign and malignant vertebral compression fractures: comparison with magnetic resonance imaging

Abstract: PurposeThe purpose of this study was to evaluate the differential diagnostic value of 2-[fluorine-18]-fluoro-2-deoxy-d-glucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) for benign and malignant vertebral compression fractures (VCFs), where the diagnostic accuracy of 18F-FDG PET/CT was compared with magnetic resonance imaging (MRI).Patients and methodsBetween 2015 and 2017, we retrospectively evaluated 87 patients with 116 VCFs. MRI was performed in all the 87 patients, whereas 18F-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…In literature, other imaging modalities have been employed for the evaluation of spinal lesions. He et al investigated the differential diagnostic value of f-18 fluorodeoxyglucose PET/CT for the benign and malignant vertebral lesion [43]. They reported on the usefulness of both maximum standardized uptake value and uptake pattern for differentiation of benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, other imaging modalities have been employed for the evaluation of spinal lesions. He et al investigated the differential diagnostic value of f-18 fluorodeoxyglucose PET/CT for the benign and malignant vertebral lesion [43]. They reported on the usefulness of both maximum standardized uptake value and uptake pattern for differentiation of benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Combined PET/CT has increased diagnostic value, but it is commonly associated with a general increase in the radiation dose received by the patient (12). To be competitive with the evolution of nonionizing imaging techniques, PET/CT needs to develop constantly, with dose reduction as one of the main goals (13)(14)(15).…”
Section: Hybrid Imaging Pet/ctmentioning
confidence: 99%
“…Recently, it has been reported that simultaneous 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG-PET) can be used to determine therapeutic response in spinal infections. 18 F-FDG-PET is less affected by other physical conditions and shows more objective results compared with blood inflammatory markers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that simultaneous 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG-PET) can be used to determine therapeutic response in spinal infections. 18 F-FDG-PET is less affected by other physical conditions and shows more objective results compared with blood inflammatory markers [9]. Several studies have shown a higher diagnostic accuracy in detecting residual infectious lesion by measuring the degree of 18 F-FDG uptake on 18 F-FDG-PET than by using CRP and MRI [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation